SINERGI ZAKAT, EKONOMI DAN EDUKASI: MEMBEDAH FAKTOR-FAKTOR PENENTU TINGKAT KEMISKINAN DI ACEH - Riza Amalia; Metasari Kartika; Romi Suradi; Abd Mubaraq (Faculty of Islamic Business and Management, 2025)
Aceh is a province in Indonesia with a Muslim-majority region and applies special autonomy and qanun, but there is a paradoxical phenomenon in this region where a significant increase in zakat distribution, economic growth, and education is actually followed by an increase in the number of poor people. This study aims to test and analyze the effect of zakat, economic growth and education on poverty rates in 23 districts / cities of Aceh Province in 2011-2021. The research method used in this study is using a descriptive quantitative approach using secondary data. The analysis technique uses panel data regression which includes cross section data (23 districts / cities) and time series data (2011-2021). Data obtained from the official websites of Baitul Mal Aceh and the Central Bureau of Statistics of Aceh Province. The results showed that zakat and education partially had a significant negative effect on the poverty rate in Aceh, this identified that zakat and education succeeded in reducing poverty in Aceh. However, it is different with economic growth where the results show that partially economic growth has a positive but insignificant effect on the poverty rate. This indicates that an increase in economic growth causes an increase in the poverty rate in Aceh. Simultaneously, zakat, economic growth and education variables together have a significant effect on poverty reduction in Aceh.